2005
DOI: 10.1021/jo0483365
|View full text |Cite
|
Sign up to set email alerts
|

The First Regioselective Metalation and Functionalization of Unprotected 4-Halobenzoic Acids

Abstract: [reaction: see text] By treatment with s-BuLi, s-BuLi/TMEDA, or t-BuLi at approximately -78 degrees C, 4-fluoro- and 4-chlorobenzoic acids (1a,b) are metalated preferentially in the position adjacent to the carboxylate. A complete reversal in regioselectivity is observed for 1a when treated with LTMP; a sequential process involving a rapid intraaggregate lithiation through a quasi dianion complex "QUADAC" is postulated to explain the unusual reactivity of Me(2)S(2) and I(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…[8] The metalation of 4-fluoro-and 4-chlorobenzoic acids 2a, 2b results in exclusive reaction ortho to the carboxylate with sBuLi, sBuLi/TMEDA, or tBuLi, but LTMP selectively metalates the C3-positions. [9] These results corroborate the concept of the achievement of regiocontrol in hy-Metalation of Unprotected Biphenyl-2-, -3-, and -4-carboxylic Acids FULL PAPER drogen/metal exchange processes through mechanism-based matching of substituents and reagents. [10] Here we report on the reactivity of biphenyl-2-, -3-, and -4-carboxylic acids 3-5 towards sterically hindered lithium amides, alkyllithiums, and LICKOR.…”
supporting
confidence: 77%
“…[8] The metalation of 4-fluoro-and 4-chlorobenzoic acids 2a, 2b results in exclusive reaction ortho to the carboxylate with sBuLi, sBuLi/TMEDA, or tBuLi, but LTMP selectively metalates the C3-positions. [9] These results corroborate the concept of the achievement of regiocontrol in hy-Metalation of Unprotected Biphenyl-2-, -3-, and -4-carboxylic Acids FULL PAPER drogen/metal exchange processes through mechanism-based matching of substituents and reagents. [10] Here we report on the reactivity of biphenyl-2-, -3-, and -4-carboxylic acids 3-5 towards sterically hindered lithium amides, alkyllithiums, and LICKOR.…”
supporting
confidence: 77%
“…2, 133.5, 132.5, 129.4, 127.0 (d, J = 8.0 Hz), 115.1 (d, J = 21.0 Hz), 72.1, 70.5, 37.4, 27.8, 22.4, 14.0;IR (KBr): ν 3545, 2937, 1610, 1512, 1440, 1221, 1054 7, 138.1, 136.9, 134.8, 133.4, 133.2, 129.6, 126.6, 113.6, 72.6, 55.2, 47.6, 32.2, 24.9;IR (neat): ν 3457, 2955IR (neat): ν 3457, , 2903IR (neat): ν 3457, , 2830IR (neat): ν 3457, , 1609IR (neat): ν 3457, , 1583IR (neat): ν 3457, , 1511IR (neat): ν 3457, , 1443IR (neat): ν 3457, , 1247IR (neat): ν 3457, , 1180IR (neat): ν 3457, , 1081IR (neat): ν 3457, , 1029 2, 138.2, 138.0, 136.9, 134.9, 133.5, 129.7, 129.6, 128.2, 128.0, 126.0, 122.3, 72.8, 47.6, 32.2, 24.9, 21.5;IR (neat): ν 3430, 2898IR (neat): ν 3430, , 1577IR (neat): ν 3430, , 1451IR (neat): ν 3430, , 1276IR (neat): ν 3430, , 1150IR (neat): ν 3430, , 1073IR (neat): ν 3430, , 1035 8, 146.7, 138.0, 137.0, 135.2, 134.8, 133.4, 129.8, 129.7, 118.6, 108.0, 106.3, 101.0, 72.7, 47.6, 32.2, 24.9;IR (KBr): ν 3425, 2882, 1682, 1501, 1485, 1441, 1238, 1041 2, 138.1, 136.82, 136.80, 134.8, 133.4, 129.59, 129.55, 128.9, 125.2, 72.7, 47.6, 32.1, 24.9, 21.0;IR (neat): ν 3572, 3457, 2898IR (neat): ν 3572, 3457, , 1906IR (neat): ν 3572, 3457, , 1572IR (neat): ν 3572, 3457, , 1506IR (neat): ν 3572, 3457, , 1440IR (neat): ν 3572, 3457, , 1276IR (neat): ν 3572, 3457, , 1079 …”
Section: General Informationmentioning
confidence: 99%
“…1, 136.9, 134.9, 133.4, 129.7, 129.6, 128.2, 127.1, 125.2, 72.7, 47.6, 32.1, 24.9; IR (KBr): ν 3545, 3063, 2937, 1577, 1501, 1451, 1276, 1183, 1084, 700 cm −1 ; HRMS calcd for C 17 H 16 Cl 2 NaOS 2 (M + Na) +…”
mentioning
confidence: 99%
“…However, the description of the preparation of different fluorinated benzoic acids (except 4-fluorobenzoic acid) has not been published until 2007 [11]. Comparison of our preparative results [11] with the reported routes for the synthesis of these products [19][20][21][22] revealed that a universal method of synthesis of different fluorosubstituted benzoic acids from available raw materials with good yields has been elaborated for the first time. High selectivity of carbonylation of these substrates (95-100%) and excellent preparative yields (85-95%) can serve in favor of S RN 1 mechanism.…”
Section: Introductionmentioning
confidence: 83%